Women in Mount Tengger Folklores: Their Presence, Position and Environmental Knowledge of Disaster Mitigation - Sony Sukmawan; Lestari Setyowati (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2021)
Tenggerese people in East Java are one of Indonesia’s ethnic communities endowed with a unique folklore. This ethnographic research aimed to find out 1) how women are presented in Mount Tengger folklore; 2) the position of women in Tengger folkore; and 3) Tenggerese women’s environmental knowledge in relation to nature and disaster mitigation. Data analysis used multi perspective dimensions by employing theories of ecofeminism, ecocriticism, and folkloristic views. Human instruments, observations, interviews, and documentation were used in this study. The findings revealed that 1) women are presented both in Tengger folktales and oral poetry (spells), and are characterized as being mentally strong, respected, and having the proclivity to protect the environment. 2) In Tenggerese folklore, women enjoy equal position with men. The equality between men and women has become a social value and practice within Tenggerese traditions. Women work side-by-side with men in their domestic lives and beyond. 3) Tenggerese women have extensive environmental knowledge, in both the physical and psychological sense. They have in-depth and detailed knowledge of the vitality of nature for human living.